Epidemiology of hepatitis C virus infection in the world, Europe, Italy and Campania: an overview (Italian Journal of Public Health, 2004)
HCV infection is today the viral epidemic disease second only to AIDS. It is estimated that 3% of the worldpopulation is infected by hepatitis C and chronic related diseases, with markedly different prevalencesbetween different geographical areas and different categories in the same area.The Authors analyse the epidemiological data available to trace the situation worldwide, in Europe, in Italyand in Campania, currently and in the last few years. Also researched was the role that the risk factorsrelated to the different transmission routes play in the spread of the infection.Despite the decrease in the incidence reported in recent years, the numerous cases linked to drug abuse, toinfections occurring while in health care and after unsafe sexual intercourse reveal the need for furtherinformation to be spread on HCV infection and on its modes of transmission.
Keywords: hepatitis C; epidemiology; transmission modes